High School Dropouts and the Economic Losses from Juvenile Crime in California - Belfield, Clive R. (2009)
California’s juvenile crime rate is high. Juveniles commit one-in-six violent crimes and over one-quarter of all property crimes; they also commit crimes in school, victimizing one-quarter of all students and one-in-twelve teachers. The economic loss from juvenile crime is substantial. In total, each juvenile cohort in California imposes an economic loss of $8.9 billion on the state’s citizens. Part of the explanation for juvenile crime is poor education. In this paper, we estimate the economic loss from juvenile crime associated with not completing high school before age 18. Using results from three separate studies and applying their results for California, we estimate the annual juvenile crime loss associated with high school dropouts at $1.1 billion. Finally, we compare the losses from juvenile crime with the costs of improving the education system. We calculate that savings in juvenile crime alone will offset approximately 16% of the costs of providing these interventions